Acupuncture in Parkinson's disease (Research, Society and Development, 2021)
The study aimed to characterize the scientific production on the use of acupuncture in Parkinson's Disease. Method: Integrative literature review conducted in November 2020, in the LILACS, MEDLINE and PUBMED databases with the descriptors: Acupuncture and Parkinson's Disease. Inclusion criteria were selected for production: articles published between 2015 and 2020, in Portuguese and English and exclusion criteria: editorials, literature reviews, animal models and duplicate studies. Results: 29 articles were identified that, after reading the abstracts and titles and applying the inclusion and exclusion criteria, culminated in the selection of four articles as a sample of this study. Among the four articles, all were written in English, three were randomized studies and one was before and after; two performed the intervention for eight weeks, one for five and the other for three weeks. The studies addressed the use of acupuncture for symptoms of fatigue, sleep disorders and motor disorders and the authors concluded that acupuncture is effective in improving the quality of life of patients with Parkinson's disease. Conclusion: acupuncture is feasible to be used to alleviate Parkinson's symptoms. However, it was found that the topic is still little explored in research and points to the need for further studies to expand the scientific evidence on the effectiveness of using acupuncture as a non-pharmacological practice in the treatment of Parkinson's disease.